2008
DOI: 10.1249/01.mss.0000321639.38724.34
|View full text |Cite
|
Sign up to set email alerts
|

Association of the ACTN3 Genotype and Physical Functioning with Age in Older Adults

Abstract: Objective. The purpose of this study was to examine the association of the alpha-actinin-3 (ACTN3) R577X polymorphism on muscle function and physical performance in older adults.Methods. We measured knee extensor torque, midthigh muscle cross-sectional area, muscle quality, short physical performance battery score, and 400-meter walk time at baseline and after 5 years in white older adults aged 70-79 years in the Health, Aging and Body Composition Study cohort (n ¼ 1367). Incident persistent lower extremity li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 31 publications
1
16
0
4
Order By: Relevance
“…In a 5-year follow-up study, Delmonico et al (2008) found that XX men had higher increase in 400-m walk time compared with RR or RX men. In contrast, XX women had a greater risk of incident persistent lower extremity limitation compared to RR women.…”
Section: Longitudinal Genetic Association Studiesmentioning
confidence: 97%
“…In a 5-year follow-up study, Delmonico et al (2008) found that XX men had higher increase in 400-m walk time compared with RR or RX men. In contrast, XX women had a greater risk of incident persistent lower extremity limitation compared to RR women.…”
Section: Longitudinal Genetic Association Studiesmentioning
confidence: 97%
“…They were also unable to confirm the difference in fiber-type proportion reported by Vincent and colleagues. Interestingly, in a longitudinal study of 1367 older adults (70 -79 years), Delmonico et al 82 reported greater losses of 400 m walk time performance over 5 years in male X / X vs R-allele carriers, whereas X / X women had a 35 % greater risk of lower extremity physical limitation compared with R / R women. Judson et al 83 recently reported great risk of falling in older females carrying at least one X allele.…”
Section: Alpha Actinin 3 ( Actn3 )mentioning
confidence: 99%
“…Judson et al 83 recently reported great risk of falling in older females carrying at least one X allele. The general consensus among these studies is that ACTN3 X / X carriers have modestly lower skeletal muscle strength and power in comparison with R-allele carriers, with the work of Delmonico et al 82 and most recently Judson et al 83 indicating potential clinical importance for the X / X genotype in older men and women.…”
Section: Alpha Actinin 3 ( Actn3 )mentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 20% of the world population, and 18% of the European population, harbour the ACTN3 577XX genotype and consequently are completely deficient in ␣-actinin-3. 3 The ACTN3 R577X polymorphism has been investigated in the context of human athletic performance, in both elite endurance and power athletes, [4][5][6] and the general population, [7][8][9] with the overall conclusion that ␣-actinin-3 deficiency, as marked by the 577XX genotype, is detrimental to power performance and possibly beneficial to endurance performance. Recently, we have shown, in a large group of elite European athletes (n = 633), that 'worldclass' endurance athletes were 3.7 times more likely to harbour the 577XX genotype than national-level counterparts, and that elite power athletes were ∼50% less likely to harbour the 577XX genotype compared to sedentary controls.…”
Section: Introductionmentioning
confidence: 99%